The Role of Art in Building Social Cohesion in Multicultural Societies - Arifka, Ayu (Journal of Studies on Art, Culture and Society, 2024)
This research explores the role of art in building social cohesion in multicultural societies. Using mixed methods, namely a quantitative survey of 300 respondents from various cultural backgrounds and qualitative interviews with 20 community arts program participants, this research found that participation in arts activities significantly increases social cohesion. Types of arts such as music, dance, theater, and drama have been shown to be most effective in promoting social interaction, cultural understanding, and reducing prejudice between groups. Community arts programs have a positive impact in strengthening relationships between groups and promoting social harmony. These results underscore the importance of supporting and developing arts programs as a strategy to strengthen social cohesion in diverse communities.